Financial technology as one of the recovery strategies of the Iraqi banking sector in the post-Covid-19 stage: An exploratory study (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research aims to employ one of the most important strategies for recovery from the crisis of the Covid-19 pandemic, which ravaged the economies of the entire world and its various sectors, including the banking sector, through financial technology that is based on digital transformation to achieve financial sustainability and the creation of innovative financial value chains in light of the decline in the banking sector as a result of The negative effects of the Covid-19 pandemic, be guided by the relevant international accounting standards to control the risks associated with financial technology. To recover from the Covid-19 crisis, the research came out with a set of recommendations, most notably financial technology from the promising and fertile research currents for much future research for researchers. This is done by encouraging researchers from graduate students to delve into this topic.